Erattum: Lourenço, A.C.C., Baêta, D., Abreu, A.C.L. & Pombal Jr., J.P. (2010) Tadpole and advertisement call of Rhinella pombali (Baldissera, Caramaschi & Haddad, 2004) (Amphibia, Anura, Bufonidae). Zootaxa, 2370, 65–68. - Lourenço, A. C.c.; Baêta, D.; Abreu, A. C.l.; Pombal Jr., J. P. (Zootaxa, 2011)
(Erratum)